Factors Affecting the Amount of Marine Supply on Sondong and Gillnet Ship at UPT Fishery Port of Riau Province - Mhd. Haris Amin; Jonny Zain; Bustari Bustari (Tropical Marine Enviromental Sciences, 2023)
The purpose of this study was to determine the factor of the need for supplies at sea in sondong boats and gillnets and to prove how strong the relationship between these variables is. This research was conducted in January 2022 at the UPT Fisheries Port of Riau Province using the survey method. The results showed that the factors of ship size, length of time at sea, and engine power had a strong effect on the amount of fuel carried. Based on the F-test with a confidence level of 87.1%. According to the T-test, the length of time at sea has the greatest influence, while for the application of ice, the factors of length of time at sea and catch greatly affect the amount of ice in the T-test with a confidence level (coefficient of determination) of 46.7%. According to the T-test, the length of time at sea has the greatest effect on the ice supply on the sondong ship. In gill nets, boat sizes, length of time at sea, and engine power have a strong effect on the amount of fuel carried. Based on the F test with a confidence level of 91.5%. According to the T-test, the length of time at sea has the greatest effect. Whereas in the provision of ice in gill net vessels, the length of time at sea and the catch also greatly affect the amount of ice carried with a confidence level (coefficient of determination) of 88%. According to the T-test, the length of time at sea has the greatest effect on the supply of ice in gill net boats